2007
DOI: 10.1080/03602550701298663
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electron Beam Irradiation and Coupling Agents on the Thermal Stability of Sugar Cane Bagasse Fiber-Thermoplastics Scrape Composite

Abstract: The influence of blending of sugar cane bagasse with thermoplastics scrape as well as incorporation of some coupling agents has been conducted using thermogravimetric analysis (TGA). In addition, the effect of electron beam preirradiation of low density polyethylene on the properties of the bagasse-LDPE composite was also studied. Simulation of TGA data reveals that the presence of bagasse fiber accelerates the volatilization of either polypropylene or polyvinylchloride. On the other hand, polyethylene and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The results showed that the bagasse in the polymer composite improved the flexural strength, Izod impact strength, Charpy impact strength, and heat distortion temperature, but the tensile strength of the polymer composite decreased after the addition of bagasse in the polymer blend. Thermoplastic scraper composites were prepared from low-density polyethylene and sugarcane bagasse by electron beam pre-irradiation [10]. The results demonstrated that the addition of a mixture of pentaerithrol tetraacrylate and dicumyl peroxide as coupling agents improved the thermal stability of low density polyethylene.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the bagasse in the polymer composite improved the flexural strength, Izod impact strength, Charpy impact strength, and heat distortion temperature, but the tensile strength of the polymer composite decreased after the addition of bagasse in the polymer blend. Thermoplastic scraper composites were prepared from low-density polyethylene and sugarcane bagasse by electron beam pre-irradiation [10]. The results demonstrated that the addition of a mixture of pentaerithrol tetraacrylate and dicumyl peroxide as coupling agents improved the thermal stability of low density polyethylene.…”
Section: Introductionmentioning
confidence: 99%
“…Electron beam irradiated low-density polyethylene is used to prepared bagasse composites. 81 It is found that the effect of irradiation on the thermal stability is insignificant. 81 It seems that low irradiation dose is not enough to improve thermal stability.…”
Section: Modification and Additivesmentioning
confidence: 99%
“…81 It is found that the effect of irradiation on the thermal stability is insignificant. 81 It seems that low irradiation dose is not enough to improve thermal stability. 81 On the other hand, irradiation has pronounced effects on mechanical properties.…”
Section: Modification and Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the previous study, results show that CCF introduced to low density polyethylene (LDPE) and wax in certain composition improves tensile strength and hardness . Adding the CCF to LDPE improves thermal stability of the polymer [12]. If CCF is mixed with natural rubber, it will increase the tensile strength [2].…”
Section: Introductionmentioning
confidence: 99%